BCG protects against tuberculosis irrespective of HIV status: a matched case-control study in Mwanza, Tanzania. Issue 3 (24th August 2012) - Faurholt-Jepsen, Daniel; Range, Nyagosya; PrayGod, George; Jeremiah, Kidola; Faurholt-Jepsen, Maria; Aabye, Martine G; Grewal, Harleen M S; Changalucha, John; Witte, Daniel R; Andersen, Aase B; Friis, Henrik
Abstract : While BCG vaccine protects against severe tuberculosis (TB) in children, its effect against adult TB is questionable. Furthermore, it is not known if HIV co-infection modifies the effect of BCG. Among 352 pairs of Tanzanian TB cases and matched controls, the BCG scar was associated with a reduced risk of TB (OR 0.3, 95% CI 0.2 to 0.7, p=0.005), irrespective of HIV status (interaction, p=0.623). BCG vaccination considerably reduced the risk of TB, both among individuals with and without HIV infection.